Long chain fatty acids and dietary fats in fetal nutrition - Cetin, Irene (Blackwell Science Inc, 2009)
Long chain polyunsaturated fatty acids are essential nutrients for a healthy diet. The different kinds consumed by the mother during gestation and lactation may influence pregnancy, fetal and also neonatal outcome. The amount of fatty acids transferred from mother to fetus depends not only on maternal metabolism but also on placental function, i.e. by the uptake, metabolism and then transfer of fatty acids to the fetus. The third trimester of gestation is characterized by an increase of long chain polyunsaturated fatty acids in the fetal circulation, in particular docosahexaenoic acid, especially to support brain growth and visual development. These mechanisms may be altered in pathological conditions, such as intrauterine growth restriction and diabetes, when maternal and fetal plasma levels of long chain polyunsaturated fatty acids undergo significant changes. The aim of this review is to describe the maternal and placental factors involved in determining fetal fatty acid availability and metabolism, focusing on the specific role of long chain polyunsaturated fatty acids in normal and pathological pregnancies.